Socioeconomic inequalities in the uptake of maternal healthcare services in Ethiopia - Markos Mezmur; Kannan Navaneetham; Gobopamang Letamo; Hadgu Bariagaber (BMC, 2017)
Abstract Background The progress in coverage of maternal health services in Ethiopia has been rather slow over the past decade and consequently the maternal mortality ratio was very high (673 per 100,000 live births) among the countries in Sub-Saharan Africa and remained constant during 2005-11 period. Earlier studies have mostly focused on determinants of maternal health seeking behavior in Ethiopia. However, little is known about the inequality aspects. This study intends to examine socioeconomic inequalities in the uptake of maternal health services and to identify factors that contribute to such inequalities. Methods Data for the study is drawn from three rounds (year 2000, 2005 and 2011) of the Ethiopian Demographic and Health Surveys (EDHS). Concentration curves and the related concentration index (CI) were used to capture inequalities across the full range of socioeconomic status and highlight trends in the uptake of maternal health services in the country. Decomposition analysis was also employed to identify dominant factors that contribute to inequalities in the uptake of maternal healthcare services. Results In this study, there is a general improvement in the uptake of maternal health services in Ethiopia over the past decade which is inequitable to the disadvantage of the poor. Inequalities are much larger in care during giving birth than in other maternal healthcare indicators. Furthermore, despite the progress made in reducing inequalities in the uptake of four antenatal care consultation (ANC) and tetanus toxoid (TT) injection, inequalities in access to health facilities for delivery and skilled assistance during delivery have rather widened over the same period. In all the survey years, inequalities in education and media access significantly contribute to inequalities in maternal health service utilization favoring the non-poor. Conclusion The challenges to improving the uptake of maternal healthcare services in Ethiopia go beyond improving coverage of the maternal health services. Thus, addressing socioeconomic inequalities in accessing maternal health services is central to resolving challenges of maternal health. Furthermore, as Ethiopia moves forward with the sustainable development agenda, socioeconomic inequalities in uptake of maternal health services should also be continuously monitored.